Pembiasaan Karakter Santun dalam Didikan Program “Sabtu Berkarakter” di TPQ Nurun Ni’mah - Tasliyatun Nimah; Ahmad Hilal Madjdi (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2023)
Early childhood is characterized by spontaneous behavior, both in activities and interactions with others. Young children still require adults who can directly demonstrate and inform them about socially acceptable behavior. This study aims to analyze the influence of the “Saturday Character” program in shaping polite character among students at TPQ Nurun Ni’mah. The research adopted a descriptive study with a qualitative descriptive approach. The research was conducted at TPQ Nurun Ni’mah, involving participants consisting of students who participated in the Saturday Character program. Key informants included 8 educators an 45 students, while supplementary informants included the students’ parents. Data were collected through interviews, observations, and document analysis. The result of the study revealed that the cultivation of polite character through the “Saturday Character” program at TPQ Nurun Ni’mah proved to be effective in shaping polite behavior among students.